Endothelial PD‐1 Regulates Vascular Homeostasis and Oligodendrogenesis during Brain Development - Tingting He; Mengtian Zhang; Jie Qin; Yanyan Wang; Sihan Li; Chaoyi Du; Jianwei Jiao; Fen Ji (Advanced Science)
Abstract Appropriate vascular and neural development is essential for central nervous system (CNS). Although programmed cell death receptor 1 (PD‐1) mediates neurogenesis, its role in cerebrovascular development remains poorly understood. Here, a correlation between cerebral vessels and oligodendrocyte precursor cells (OPCs) is revealed during brain development. The ablation of endothelial PD‐1 triggers cortical hypervascularization through excessive angiogenic sprouting, concomitantly driving OPC differentiation. These alterations disrupt blood brain barrier (BBB) maturation, induce dysmyelination, and ultimately result in abnormal behavior in mice. Mechanistically, the loss of endothelial PD‐1 suppresses the activity of the Wnt/β‐catenin signaling pathway, thereby disrupting normal angiogenesis. Concurrently, it activates the MEK1/2‐ERK1/2‐GLI1 pathway, leading to increased GREMLIN1 (GREM1) expression. Elevated GREM1 secretion inhibits the BMP/SMAD1/5/SMAD4 signaling cascade in OPCs, which inhibits oligodendrogenesis and myelination. These findings indicate the importance of endothelial cell‐intrinsic PD‐1 in regulating the oligovascular niche, and suggest potential therapeutic implications for neurological disorders associated with disrupted vascular development.